History, recent development and uses of Finnsheep - Maijala, K. (Agricultural and Food Science, 1988)
The use of Finnsheep (F) as experimental animals on fertility has created interest in the origin of it and its prolificacy. Linguistic and archeological evidence indicate that wool has been used in Finland for 2 000 years and that sheep have been kept for over 1 000 years. The ancestors of F may have arrived either with Finns from the present Russia, where the short-tailed and prolific Romanov breed is found, or with Vikings or western settlers from Scandinavia, where there also are short-tailed breeds. Finnish terms concerning weaving (mainly Slavic loans) speak for the former, the sheep husbandry terms (mainly Germanic loans) for the latter source. In the 16th and 18th centuries, foreign breeds were imported to western Finland, but they were not accepted by farmers. When animals from northeastern Finland were mainly used as foundations for the herd book work, the present F may stem mainly from the original stock. The breed has long been kept in small flocks and thus been subject of inbreeding and weak selection. Since the establishment of herd book and production recording the live and fleece weights as well as litter sizes have increased. Wool was the main product until the 1920’s, but meat has been most important during the last 60 years, excepting war times. Presently one aims at effective utilization of its versatility, i.e. for meat, handicraft wool, luxury furs, and forest and landscape management.